PENERAPAN AKUNTANSI DENGAN METODE ACCRUAL BASIS PADA UKM BATIK MALANGAN KELURAHAN BANDUNGREJOSARI MALANG - Risnaningsih .; Hendrik Suhendri (REFORMASI, 2015)
Generally, UKM in Indonesia have not been held and the maximum use of accounting information in the management of its business (Rochmat, 2003; Fansuri, 2006; Firdaus, 2010; Hubeis, 2012). As same as UKM Batik Malangan who has not been organized and use accounting information maximally. The purpose of this study was to determine whether UKM Batik Malangan Kelurahan Bandungrejosari Malang has implemented accrual basis accounting method or not.This type of research is a descriptive research. The location that used in this research are UKM Batik Malangan Kelurahan Bandungrejosari Malang. The technical of collecting data that used in this study was a questionnaire, observation, interview and documentation. Data analysis method that used in this study is distributing questionnaires to the respondents, the questionnaire process and conclude whether UKM Batik Malangan already implementing accrual accounting method or not. The results showed that UKM Batik Malangan did not apply accrual accounting method. All this time, UKM have not made a financial statement, and to determine the profit or loss obtained each year, UKM Batik Malangan only calculate the amount of income is reduced by the costs incurred. So as to obtain additional capital from bank loans, UKM Batik Malangan has hard problem, as all this time they have not implement accounting.